Linking Transformation and Problem Atomization in Algebraic Problem-Solving - Tomáš Lengyelfalusy; Dalibor Gonda (Mathematics, 2023)
The transition from arithmetic to algebra requires students to change both their thinking and the way they learn. We often observe students using arithmetic formalism also when solving algebraic problems. This formalism manifests itself primarily in the acquisition of coherent computational procedures. Students must be sufficiently aware that the computation steps are sequential transformations of the problem. This creates a problem for them in solving more complex problems. Our research investigated whether problem transformation coupled with atomization is a suitable alternative for students to learn coherent algorithms. Although atomization is not based on precise rules, it was reported by students to be a comprehensible way of solving problems and providing them with sufficient confidence. If students are motivated to understand a computational method, this understanding represents fulfilling the student’s need for security.